AESTHETICS OF PLAK-PLIENG GRAVESTONE OF LAMURI KINGDOM ACEH: A STUDY ACCORDING TO SUSANNE KNAUTH LANGER'S AESTHETIC CONCEPT - Rosaguna, Rajes Ikhlas; Purba, Mauly; Priyatno, Agus (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2024)
The Lamuri Kingdom in Aceh has relics in the form of gravestones called "Plak-plieng" stones, which are concrete evidence and records of the history of the kings who were buried with these gravestones. This Plak-plieng gravestone is thought to be a gravestone made by local people during the reign of the Lamuri kingdom with a mixed population who emigrated from outside Aceh at that time. The Lamuri Kingdom was an Acehnese Hindu kingdom that existed in the 4th century, turned into Islam or a sultanate in the 9th century, and lasted until the 15th century. The Plak-plieng gravestone, which is characteristic of the Lamuri royal graves, was rediscovered in 1890. Based on the date written on the gravestone found, the Plak-plieng gravestone dates to the 12th century AD. Thus, the Plak-plieng gravestone was made during the Islamic era, or when Lamuri became an Islamic kingdom. The type of research in this study is research using a descriptive method. The descriptive method is a method used to look for elements, characteristics, and properties of a phenomenon. The method begins with collecting data, analysing the data, and interpreting it. This descriptive research tries to reveal and explain the problems that occur in society, especially the problem of searching for symbolic aesthetics on the Plak-plieng gravestones of the Lamuri kingdom of Aceh. The Plak-plieng gravestone contains various symbolic elements that we can find using Susane K. Langer's theory. The findings of the symbolic aesthetic meaning found are divided into several parts according to Langer's aesthetic theory. On the Plak-plieng gravestones of the Lamuri Kingdom of Aceh, symbolic aesthetics are found as a symbol of art. The implied value of this gravestone gives us an idea of the high artistic value that existed in past societies. In this way, we can see that the level of artistic taste of the people of Aceh in the past was very high. The discovery of the inscription on this gravestone also explains the glory days of a kingdom led by the owner of the gravestone. This day dates back nine hundred years. In this way, we can learn about the value of art in the past through the Acehnese civilisation and how they found materials for making sturdy gravestones and a variety of ornaments that were very complicated and beautiful.